Antigen Presenting Cells and Stromal Cells Trigger Human Natural Killer Lymphocytes to Autoreactivity: Evidence for the Involvement of Natural Cytotoxicity Receptors (NCR) and NKG2D - Alessandro Poggi; Maria Raffaella Zocchi (Clinical and Developmental Immunology)
Human natural killer (NK) lymphocytes should not damage autologous cells due to the engagement of inhibitory receptor superfamily (IRS) members by HLA-I. Nevertheless, NK cells kill self cells expressing low levels or lacking HLA-I, as it may occur during viral infections (missing-self hypothesis). Herein, we show that human NK cells can be activated upon binding with self antigen presenting cells or stromal cells despite the expression of HLA-I. Indeed, NK cells can kill and produce pro-inflammatory and regulating cytokines as IFN-γ, TNF-α and IL10 during interaction with autologous dendritic cells or bone marrow stromal cells or skin fibroblasts. The killing of antigen presenting and stromal cells is dependent on LFA1/ICAM1 interaction. Further, the natural cytotoxicity receptors (NCR) NKp30 and NKp46 are responsible for the delivery of lethal hit to DC, whereas NKG2D activating receptor, the ligand of the MHC-related molecule MIC-A and the UL16 binding protein, is involved in stromal cell killing. These findings indicate that different activating receptors are involved in cell to self cell interaction. Finally, NK cells can revert the veto effect of stromal cells on mixed lymphocyte reaction further supporting the idea that NK cells may alter the interaction between T lymphocytes and microenvironment leading to autoreactivity.